The Role of Tiktok Travel Vlogs on Interest in Visiting Surabaya’s Mangrove Botanical Garden: Peran Travel Vlog Tiktok terhadap Minat Berkunjung ke Kebun Raya Mangrove Surabaya - Irma Indana Zulfa; Taufik Setyadi; Gyska Indah Harya (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
The transformation of TikTok social media into a major platform for the dissemination of travel vlog content has changed the way tourists search for destination references through authentic and attractive visualizations. Surabaya Mangrove Botanical Garden was chosen as the object of this study due to its status as a conservation area and ecotourism destination that requires an appropriate digital promotion strategy to reach a wider audience. This study aims to determine the influence of TikTok travel vlogs on interest in visiting Surabaya Mangrove Botanical Garden. The method used in this study is quantitative, where questionnaires serve as the main tool for data collection. The sample consisted of 120 respondents selected through purposive sampling, with the criteria being TikTok accounts that had watched travel vlogs about the Surabaya Mangrove Botanical Garden and had never visited the tourist destination. The data obtained was analyzed using Structural Equation Model (SEM) with the help of SmartPLS 4.0 software. The results showed that TikTok travel vlogs had a positive and significant effect on interest in visiting. This study has practical implications for the Surabaya Mangrove Botanical Garden to optimize its marketing strategy through TikTok social media to increase the number of visitors.